Aberrant MicroRNAomics in Pulmonary Complications: Implications in Lung Health and Diseases - Rajib Kumar Dutta; Srinivasan Chinnapaiyan; Hoshang Unwalla (Elsevier, 2019)
Over the last few decades, evolutionarily conserved molecular networks have emerged as important regulators in the expression and function of eukaryotic genomes. Recently, miRNAs (miRNAs), a large family of small, non-coding regulatory RNAs were identified in these networks as regulators of endogenous genes by exerting post-transcriptional gene regulation activity in a broad range of eukaryotic species. Dysregulation of miRNA expression correlates with aberrant gene expression and can play an essential role in human health and disease. In the context of the lung, miRNAs have been implicated in organogenesis programming, such as proliferation, differentiation, and morphogenesis. Gain- or loss-of-function studies revealed their pivotal roles as regulators of disease development, potential therapeutic candidates/targets, and clinical biomarkers. An altered microRNAome has been attributed to several pulmonary diseases, such as asthma, chronic pulmonary obstructive disease, cystic fibrosis, lung cancer, and idiopathic pulmonary fibrosis. Considering the relevant roles and functions of miRNAs under physiological and pathological conditions, they may lead to the invention of new diagnostic and therapeutic tools. This review will focus on recent advances in understanding the role of miRNAs in lung development, lung health, and diseases, while also exploring the progress and prospects of their application as therapeutic leads or as biomarkers. Keywords: microRNA dysregulation, COPD, cystic fibrosis, lung cancer, asthma, idiopathic pulmonary fibrosis, antagomiR, aptamer